Bioeconomic Performance of Pullets and Layer Hens Fed Soybean Grains-Based Diets in Hot and Humid Climate - HOUNDONOUGBO, M. FRÉDÉRIC; CHRYSOSTOME, CHRISTOPHE ACHILLE A. MAHUSSI; DAGA, DADJO FLORIAN; ADJAHO, S L (My University, 2012)
The aim of this paper was to evaluate the effects of toasted soybean grains on bioeconomic performance of pullets and layer hens in hot and humid environment. A total of 972 three-week-old Harco chicks were divided into 12 groups. At starter, pullet and laying phases, birds were fed four diets containing 0% (R0), 5% (R5), 10% (R10), and 15% (R15) of soybean grains. Results showed similar feed intake, body weight gain, laying rate, feed conversion ratio, and mortality rate between dietary treatments at each phase. The egg weight increased significantly in diet R15 (P < 0.05). The use of soybean grains reduced the feed prices. Feeding cost decreased significantly (P < 0.05) during growth and laying phases in soybean grains added diets. Feeds efficiency increased significantly (P < 0.05) with the increase of dietary soybean grains rate. Properly toasted soybean grains can be therefore included up to 15% in heavy line layer hens’ diet in tropical conditions.
Keywords: Pullet; Layer; Sya bean; bioeconomic performance